An Invitro Comparative study of The Effect of the Dental Bleaching on Microleakage around Resin Composite Restorations Using two Defferent Adhesive Systems (Journal of Hama University, 2021)
the aim of this study was to evaluate how postoperative bleaching affected microleakage of resin composite restorations bonded with two adhesive systems (Total-Etch ,Universal).40 permanent molar were used, and standardized class V cavity preparation were made on the buccal and lingual surfaces (80 class V). the teeth were restored with composite (Tetric N Ceram, Ivoclar Vivadent) and divided into four groups according to the adhesive systems (fifth generation Tetric N Bond Total-Etch, eighth generation Tetric N Bond, Universal) and the bleaching procedure(Total Blanc Office, H\35, NOVA, DFL) :1- fifth generation bonding agent with no bleaching of samples.2- eighth generation bonding agent with no bleaching of samples. 3- fifth generation bonding agent with bleaching.4- eighth generation bonding agent with bleaching.The teeth were immersed in dye, then sectioned and dye penetration was scored. The appropriate statistical analysis were done.analysis showed statistically differences between the bleached groups and the non-bleached groups (P0,05) Result of this study showed that bleaching agents significantly affect on the microleakage around composite restorations and the adhesive systems had no significant effect in preventing microleakage.